The NLRP3 and Pyrin Inflammasomes: Implications in the Pathophysiology of Autoinflammatory Diseases - de Torre-Minguela, Carlos; Mesa del Castillo, Pablo; Pelegrín, Pablo (Frontiers in Immunology, 2017)
Inflammasomes are multiprotein complexes that critically control different aspects of innate and adaptive immunity. Among them we could highlight the release of pro-inflammatory cytokines that induces and maintains the inflammatory response. Usually, inflammasomes results from oligomerization of a nucleotide-binding domain-like receptor (NLR) after sensing different pathogenic or endogenous sterile dangerous signals; however other proteins as AIM2, RIG-I or Pyrin could also form inflammasome platforms. Inflammasome oligomerization leads to caspase-1 activation and the processing and release of the pro-inflammatory cytokines interleukin (IL)-1 and IL-18. Mutations in different inflammasomes are causative for multiple periodic hereditary syndromes or autoinflammatory diseases, characterized by acute systemic inflammatory flares not associated to infections, tumors or autoimmunity. This review focus on germline mutations that have been described in cryopyrin-associated periodic syndrome (CAPS) for NLRP3 or in familial Mediterranean fever (FMF) and Pyrin associated autoinflammation with neutrophilic dermatosis (PAAND) for MEFV. Besides the implication of inflammasomes in autoinflammatory syndromes, these molecular platforms are involved in the pathophysiology of different illnesses, including chronic inflammatory diseases, degenerative processes, fibrosis or metabolic diseases. Therefore, drug development targeting inflammasome activation is a promising field in expansion.